The extracellular matrix in peripheral nerve repair and regeneration: a narrative review of its role and therapeutic potential - Metafune, Miriam; Muratori, Luisa; Fregnan, Federica; Ronchi, Giulia; Raimondo, Stefania (Frontiers in Neuroanatomy, 2025)
The extracellular matrix (ECM) is a non-cellular and gelatinous component of tissues, rich in proteins and proteoglycans, that provides information about the environment, forms a reservoir of trophic factors and regulates cell behavior by binding and activating cell surface receptors. This important network acts as a scaffold for tissues and organs throughout the body, playing an essential role in their structural and functional integrity. It is essential for cells to connect and communicate with each other and play an active role in intracellular signaling. Due to these properties, in recent decades the potential of the extracellular matrix in tissue engineering has begun to be explored with the aim of developing innovative biomaterials to be used in regenerative medicine. This review will first outline the components of the extracellular matrix in the peripheral nerve, followed by an exploration of its role in the regeneration process after injury, with a focus on the mechanisms underlying its interactions with nerve cells. Qualitative and quantitative methods used for extracellular matrix analysis will be described, and finally an overview will be given of recent advances in nerve repair strategies that exploit the potential of the extracellular matrix to enhance regeneration, highlighting the critical issues of extracellular matrix molecule use and proposing new directions for future research.